Fenomena Pesta Pernikahan Adat Dayak di Tengah Keragaman Beragama - Husnun Nahdhiyyah (State Islamic University (UIN) of Sunan Ampel, 2021)
Legal marriages according to Islamic law are not necessarily legal according to Dayak customary law. The bride and groom must hold a traditional Dayak wedding ceremony in which there are things that are contrary to Islamic law, such as cutting pigs, wine and begendang party. This study is a qualitative research with symbolic interpretative approach using observation, interviews and documentation in the data collection. Primary data were directly obtained from interviews with religious leaders, Dayak traditional demons and Dayak indigenous people. There are three variants of the views of the Muslim Dayak community on the traditional Dayak Sungai Melayu Rayak wedding ceremony procession, namely: theological normative, sociological normative and sociological empirical. There are two categories and philosophical reasons for the preservation of the traditional wedding ceremony procession by the Dayak religious Leaders and Demong Dayak Adat Melayu Sungai Rayak, namely internal and external. Internal reasons include: the sacredness of marriage, the commitment of marriage, the practice of plurality in the family and the procession of the traditional wedding ceremony that is a culture that needs to be preserved and maintained because it can create inter-religious harmony. While external reasons include: avoiding the moral sanction that is not recognized, social sanctions are excluded, namely economic sanctions imposed fines and the last is controlling.